IL-6 after wake-up in human males: Exposure to red versus blue light and the interplay with cortisol - Mekschrat, Liza; Schmalbach, Bjarne; Rohleder, Nicolas; Petrowski, Katja (Brain, Behavior, & Immunity-Health, 2024)
Light is essential in shaping human circadian rhythms, including that of the hormone cortisol. While cortisol is known to influence secretion of the cytokine IL-6, the influence of light itself on IL-6 remains unclear. Thus, this study investigated the effects of two light conditions – red and blue – on IL-6 concentrations and the cortisol awakening response in blood. The interplay between cortisol and IL-6 was explored as well. The between-subject experiment was conducted with 71 healthy adult men (aged Mred = 24.30, SD = 3.56; Mblue = 24.40, SD = 3.51) in a standardized sleep laboratory setting with 60-min light exposure post-awakening at 05:00 a.m. Two mixed models, with light condition and time across measurement points as factors, were calculated. In the one for cortisol, chronotype was introduced as a covariate. Mean cortisol concentrations did not differ between exposure to red vs. blue light (p = 0.443), but overall cortisol output (area under the curve with respect to ground; AUCG) and sensitivity (area under the curve with respect to increase; AUCI) were greater in the blue-light condition (p = 0.050 and p < 0.001, respectively). Additionally, chronotype significantly influenced cortisol concentrations (p = 0.035). As for IL-6, a main effect of time was obtained, with increasing concentrations over time (p = 0.002). Total IL-6 secretion was greater under blue-light exposure (p <. 001), but mean IL-6 concentrations (p = 0.230) and IL-6 sensitivity (p = 0.777) did not differ between the red- and blue-light condition. Mean and total cortisol and IL-6 concentrations were significantly negatively correlated (p = 0.021 and p < 0.001, respectively) during the red-light exposure. In the blue-light condition, cortisol sensitivity was significantly negatively correlated with IL-6 sensitivity (p = 0.034). Overall, blue light seemed to have exerted a greater influence on cortisol and IL-6. For cortisol, this effect might be moderated by chronotype. Additionally, cortisol and IL-6 seem to interact under light exposure. However, these effects were mixed and could not be found consistently across mean secretion, AUCg and AUCi.
CRIS-Team Scopus Importer:2024-11-29
Keywords: Circadian rhythm; Cortisol; Cortisol awakening response; Cortisol cytokine interplay; IL-6; Inflammatory immune system; Light exposure; Sleep